Η Βυζαντινή Οικογένεια των Αγιοθεοδωριτών (ΙΙI) - ΜΑΔΑΡΙΑΓΑ, Ελισάβετ (Byzantina Symmeikta, 2017)
This paper is the third and last part of our prosopographical study on the Hagiotheodorites family members. Here, all known Hagiotheodorites are listed and studied in chronological order from the 12th century, during which most of the family members are active, up to the 14th century.